Analisis Kandungan Logam Berat Pada Tailing Pencucian Mangan PT.Anugerah Nusantara Sejahtera Di Kabupaten Timor Tengah Utara Provinsi Nusa Tenggara Timur - Tilda Metboki; Rika Ernawati; Nurkhamim (Retii, 2019)
Manganese leaching waste in the form of tailings consisting of water and mud containing heavy metals that can pollute the soil, water, and air. Including the metals Mn, Fe, Cu and Zn contained in wastewater. In-law No. 4 of 2009 concerning mineral and coal mining, it has been affirmed that all mining business operators must carry out good and correct mining activities. Therefore, efforts are needed to analyze the level of concentration of heavy metal content in manganese washing wastewater based on PP No. 82 of 2001 concerning Wastewater Quality Standards so that methods can be used to reduce heavy metal concentrations that exceed quality standards. To find out the level of heavy metal concentration in wastewater, laboratory analysis was carried out using the AAS method, then the waste containing heavy metals was processed using zeolite. In the manganese washing wastewater containing heavy metals Mn, Fe, Cu and Zn that exceeds the quality standard so that treatment is required using zeolite. It is known that the volume of water entering the pond II (KII) which is planned as a place of treatment with zeolite is 14,487,000 L / day, the mass of zeolite needed to reduce heavy metal content in 1 L of water is 10 gr. Thus, the zeolite mass needed on a field scale is 14,487 kg/day. Keywords: heavy metal, tailing, zeolite.